The competitiveness of the agricultural sector of the country as a factor in ensuring food security in the context of globalization and the integration of modern (Journal of Economic Research & Business Administration, 2015)
This article dedicate the analysis of the agricultural sector of the country, which is seen as a factor of competitiveness of the economy in general and food security in the country. On the basis of the data analyzed statistisechkih possibilities and potential of the country’s agriculture in the context of globalization, including in the context of regional integration in the Customs Union. It also gives examples constraining competitiveness of agriculture and the opportunities in this sector
Keywords: food security; globalization; integration; agriculture; competitiveness; agricultural products; manufacturing